2018
DOI: 10.1590/1679-78254346
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of brass properties through perforation tests using a thermal chamber for elevated temperatures

Abstract: Experimental analysis on standard brass alloy has been carried out using a high pressure gas gun. Perforation tests have been performed for a variety of impact velocities from 40 to 120 m/s in order to study the material behaviour and to define failure modes. The main aim of the study has been to provide results using an innovative thermal chamber that allows to heat specimens before impact. The range of available temperatures is from the room temperature up to 260 ˚C. The experimental study has allowed to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A SHPB must be utilized to define the strain rate sensitivity for strain rates greater than 5000 [ 40 , 41 ] ( Figure 2 ).…”
Section: Description Of the Specimen And Hopkinson Bar Device Usinmentioning
confidence: 99%
“…A SHPB must be utilized to define the strain rate sensitivity for strain rates greater than 5000 [ 40 , 41 ] ( Figure 2 ).…”
Section: Description Of the Specimen And Hopkinson Bar Device Usinmentioning
confidence: 99%
“…The new experimental results of unidirectional tests of tension and compression, allowing to estimate the material constants and to ensure accurate FE simulations, are presented in this chapter. They are complimentary to a number of dynamic perforation tests previously conducted at high impact velocity [ 9 ] in order to understand the thermo-mechanical behaviour of brass and to evaluate its mechanical properties.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Thus, running dynamic experiments with the use of a thermal chamber is a solution to avoid these limitations. Such experiments were carried out using brass and are widely discussed in [ 9 ]. Brass alloy was selected for this work since this material presents no or small strain rate sensitivity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, with a specially designed drop weight tower, the low velocity impact behavior of AA 2024-T3 aluminum and TRIP 1000 steel at − 60 °C was investigated by Rodríguez-Martínez et al [25,26]. As for studies concerning impact behavior of materials under subordnance or ordnance velocity at different temperatures, high temperature perforation by several authors were found [27][28][29][30]. Rusinek et al [27] developed a heating chamber coupled to the ballistic impact device to investigate perforation behavior of poly(methyl methacrylate) (PMMA).…”
Section: Introductionmentioning
confidence: 99%
“…Rusinek et al [27] developed a heating chamber coupled to the ballistic impact device to investigate perforation behavior of poly(methyl methacrylate) (PMMA). With the thermal chamber, Klosak et al [30] studied perforation behavior of brass alloy plates under temperatures ranging from 20 to 260 °C. Results showed that the energy absorption capacity decreased with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%